Availability of Phosphorus and Potassium and its Relationship Wiih some Important Physico-chemical Properties of some forest Soils of Pali Range, ( Shahdol, M.P). - Singh, A. K.; Prasad, Arun; Singh, Balvinder (Indian Forester, 1986)
A vailable P has a low status in the soils or Pali range (Shahdol) while status or available K is medium to high. Available P and K have a positive correlation with all the factors like clay, pH, CaCO3, organic matter and catipn exchange capacity in the soil developed over Deccan trap. While it has a negative correlation with all the above factors except organic over in the soil developed over lametas (Calcareous). In the soils developed over Gondwans sand stone, available P and K show mixed rotationship. It shows negative correlations with some factors like clay, pH, calcium carbonate etc. and positive correlation with others like organic matter and in some profiles clay C E.C etc. Hence there is a need to study to investigate responses to P application for enhancing forest productivity.